EVALUATION CHARACTERISTIC AND LEVEL OF FAMILY KNOWLEDGE REGARDING HOME CARE TREATMENT FOR STROKE PATIENTS - Pratiwi, Yuliana Wahyu; Yulidaningsih, Elok; Tunik, Tunik; Mandasari, Yuyun Putri (SYNTIFIC, 2025)
Background. Home Care Nursing is a health service carried out by professionals in the patient’s home with the aim of helping to meet the patient’s needs, which is carried out by a team of professionals involving family members as supporters in the nursing process. Knowledge about home care treatment is very important because families who have good knowledge of caring for stroke patients can help speed up the recovery process. The aim of this study was to evaluate characteristic and the level of family knowledge regarding home care for stroke patients. Research Method. The research design used a quantitative descriptive design. This study was conducted in the stroke unit room of RSUD Dr. Seodomo Trenggalek. The population of this study was 83 patients with a purposive sampling technique. The sample in this study was a family member who cared for patients at home or in a hospital, aged over 19 years, totaling 20 respondents. The instrument used was the Family Knowledge of Home Care Treatment Questionnaire. Findings. The level of family knowledge about home care for stroke patients was mostly in the sufficient category. The characteristics of the respondents were that most of them were aged 31-59 years, male, worked as entrepreneurs, had a junior high school or high school education, had no care experience, received information about caring for stroke patients, and sources of information were from nurses. Conclusion. Patients and families need to prepare for long-term care at home, and can improve the quality of care received.